2018
DOI: 10.1002/cncr.31255
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation options in pediatric and adolescent patients with cancer

Abstract: The incidence of childhood cancer has steadily increased since the 1950s, with approximately 16,000 children diagnosed each year. However, with the advent of more effective multimodal therapies, childhood cancer survival rates have continued to improve over the past 40 years, with >80% of patients now surviving into adulthood. Fertility preservation (FP) has become an important quality-of-life issue for many survivors of childhood cancer. As a result, the therapeutic options have become less gonadotoxic over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 56 publications
(168 reference statements)
0
74
0
5
Order By: Relevance
“…In pediatric oncology, developmental stages and maturity of patients vary greatly, as does risk for infertility . Additionally, fertility preservation options vary by a child's age and sex, and remain experimental for young children . Families can also be overwhelmed by fertility‐related and cancer‐related information, or parents may choose not to share such information with their child .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric oncology, developmental stages and maturity of patients vary greatly, as does risk for infertility . Additionally, fertility preservation options vary by a child's age and sex, and remain experimental for young children . Families can also be overwhelmed by fertility‐related and cancer‐related information, or parents may choose not to share such information with their child .…”
Section: Introductionmentioning
confidence: 99%
“…7 Additionally, fertility preservation options vary by a child's age and sex, and remain experimental for young children. [8][9][10] Families can also be overwhelmed by fertility-related and cancer-related information, or parents may choose not to share such information with their child. 11,12 Due to the interplay of such factors, some survivors grow up knowing that they could be at-risk for infertility, whereas others may be surprised to learn about such risk in survivorship.…”
mentioning
confidence: 99%
“…Cancer incidence in children, adolescents and young adults has seen a slight increase since the 1970s, but death rates in patients aged 0–19 years have continued to fall. Current 5‐year overall survival estimates for childhood cancer exceed 83% (around 90% for most hematological malignancies), which translates into a growing population of adult survivors . It is widely known that most cancer treatments like chemotherapy, radiotherapy or a combination of both are highly toxic to the gonads, putting girls and women of reproductive age at risk of premature ovarian insufficiency (POI) and subsequent infertility .…”
Section: Introductionmentioning
confidence: 99%
“…The protocol for medical ovarian stimulation via multiple hormonal injections and transvaginal oocyte retrieval in OC is quite similar to that of embryo cryopreservation. Its eventual use will require in vitro fertilization and clinical pregnancy rates (CPRs) range from 4% to 12%, with 36% to 61% of CPRs per subsequent transfer of frozen embryo [ 24 ]. As such, recent studies have demonstrated that transfer of embryos originated from frozen-thawed oocytes had comparable pregnancy rates compared to those using fresh oocytes [ 25 - 27 ].…”
Section: Oocyte Cryopreservationmentioning
confidence: 99%